2015
DOI: 10.1136/bmjopen-2015-007589
|View full text |Cite
|
Sign up to set email alerts
|

Association of child health and household amenities in high focus states in India: a district-level analysis

Abstract: ObjectivesTo assess household amenities in districts of high focus states and their association with child health in India.DesignThe data for the study are extracted from Annual Health Survey (AHS) and Census 2011.SettingsDistricts in high focus states in India.ParticipantsInformation regarding children below 5 years of age and women aged 15–49 has been extracted from the AHS (2010–2011), and household amenities information has been obtained from the Census (2011).MeasuresHousehold amenities were assessed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
3
3
1
Order By: Relevance
“…Finding of the present study shows the inverse relationship between district’s economic development with nutritional outcomes and also highlighted that the poor nutritional status of children was more concentrated in less developed districts of India. A similar finding was also reported by study from India along with other child health related indicators [3537]. However, the majority of the existing literatures examined the socioeconomic inequality at household level.…”
Section: Discussionsupporting
confidence: 86%
“…Finding of the present study shows the inverse relationship between district’s economic development with nutritional outcomes and also highlighted that the poor nutritional status of children was more concentrated in less developed districts of India. A similar finding was also reported by study from India along with other child health related indicators [3537]. However, the majority of the existing literatures examined the socioeconomic inequality at household level.…”
Section: Discussionsupporting
confidence: 86%
“…Intervention to increase access to livelihood can pave the way for reducing income inequality and reduce IMR. Factors related to pre-and postnatal care, e.g., ANC, safe delivery, PNC, and variables related to personal illness control such as recent episodes of ARI and diarrhea among children have statistically significant association with infant mortality, which is in concordance with other studies in India (Gokhale et al 2002;Gouda et al 2015). Interestingly, analysis reveals that labor force participation, birth weight, and birth interval were not associated with IMR in the spatial lag as well as error models.…”
Section: Discussionsupporting
confidence: 82%
“…Our attempt is consistent with recent studies that focused on exploring macro-level determinants of child health (Gouda et al 2015;Goli and Jaleel 2014;Bhattacharya and Cornilius 2011). We have tried to show that there is a high degree of spatial clustering in IMR.…”
Section: Introductionsupporting
confidence: 71%
“…A study in rural India reported that the odds of neonatal death were lower for infants born to unemployed mothers (OR=0.89) ( 29 ). A negative association was also found with infant and under-five mortality and female labour force participation in India ( 45 ). In addition our study did not find any significant association between child mortality and housing infrastructure as measured by access to safe water, clean fuel, and electricity; however, several other studies have established strong associations between poor health and poor housing and housing infrastructure ( 16 , 17 , 33 , 45 ).…”
Section: Discussionmentioning
confidence: 96%